2013
DOI: 10.1002/pssr.201308010
|View full text |Cite
|
Sign up to set email alerts
|

Advances in semiconductor nanowire growth on graphene

Abstract: Here we review the recent research activities on the epitaxial growth of semiconductor nanowires (NWs) on graphene substrates. Semiconductor NWs with quasi one‐dimensional structure have become an active research field due to their various interesting physical properties and potentials for future electronic and optoelectronic device applications, such as transistors, sensors, solar cells, light emitting diodes, and lasers. At almost the same time graphene, a two‐dimensional material made of carbon, was discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 192 publications
(202 reference statements)
1
29
0
Order By: Relevance
“…As Alaskar et al confirmed that during the GaAs van der Waals epitaxy process on multilayer graphene covered silicon substrate, the orientation of the epilayer is controlled by the underlying graphene layer despite the poor crystallinity [47]. A generic model proposed by Munshi et al can explain possible structures of semiconductor/graphene interfaces and different atomic arrangements of the semiconductor atoms on graphene [60,61]. They pointed out that the (0001) plane of a hexagonal semiconductor ((111) plane of a cubic semiconductor) is energetically preferred to nucleate on graphene due to the lattice symmetry, which subsequently determines the out-of-plane epitaxial relationship for epilayer.…”
Section: Van Der Waals Epitaxy Of Iii-nitrides On Graphenementioning
confidence: 95%
“…As Alaskar et al confirmed that during the GaAs van der Waals epitaxy process on multilayer graphene covered silicon substrate, the orientation of the epilayer is controlled by the underlying graphene layer despite the poor crystallinity [47]. A generic model proposed by Munshi et al can explain possible structures of semiconductor/graphene interfaces and different atomic arrangements of the semiconductor atoms on graphene [60,61]. They pointed out that the (0001) plane of a hexagonal semiconductor ((111) plane of a cubic semiconductor) is energetically preferred to nucleate on graphene due to the lattice symmetry, which subsequently determines the out-of-plane epitaxial relationship for epilayer.…”
Section: Van Der Waals Epitaxy Of Iii-nitrides On Graphenementioning
confidence: 95%
“…We like to look at a nanowire solar cell as typical a 2µm thick film on a silicon 59,[183][184][185][186][187] or e.g. a graphene 188,189 substrate with a nanowire filling fraction 14,69 between 10% and 20%. Since a III/V substrate constitutes the major fraction of the material cost of a III/V solar cell, elimination of the expensive substrate will substantially reduce the costs, as has been shown by the company Alta Devices for planar GaAs solar cells 167 .…”
Section: Economics Of Nanowire Solar Cellsmentioning
confidence: 99%
“…The use of inorganic semiconductors as an active material is desirable for flexible electronic and optoelectronic device applications, [1][2][3] due to the many potential advantages over organic semiconductors in terms of lifetime and efficiency. 4 However, continuous, rigid inorganic semiconductor thin films have no tolerance for mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%